2021
DOI: 10.3390/diseases9040079
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Inflammatory Pathogenesis of Colorectal Cancer

Abstract: Colorectal cancer is one of the most commonly diagnosed cancers worldwide. Traditionally, mechanisms of colorectal cancer formation have focused on genetic alterations including chromosomal damage and microsatellite instability. In recent years, there has been a growing body of evidence supporting the role of inflammation in colorectal cancer formation. Multiple cytokines, immune cells such T cells and macrophages, and other immune mediators have been identified in pathways leading to the initiation, growth, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 181 publications
(253 reference statements)
0
9
0
Order By: Relevance
“…By transferring human fecal microbiota to germ-free mice, a recent study found CRC-associated microbiota dysbiosis contributed to oncogenic epigenetic alterations by inducing more hypermethylated genes in murine colonic mucosa, and cumulative methylation index is an independent risk factor for CRC ( 156 ). In addition, many mycotoxins and fungal metabolites also directly promote carcinogenesis, for example, Candida albicans can product nitrosamine, acetaldehyde and candidalysin ( 157 ). Furthermore, a latest study has just found that not only bacterial microbiota (e.g., Fusobacterium ) but also fungal microbiota can affect chemotherapy resistance ( 158 ).…”
Section: The Role Of Clrs In Intestinal Carcinogenesismentioning
confidence: 99%
“…By transferring human fecal microbiota to germ-free mice, a recent study found CRC-associated microbiota dysbiosis contributed to oncogenic epigenetic alterations by inducing more hypermethylated genes in murine colonic mucosa, and cumulative methylation index is an independent risk factor for CRC ( 156 ). In addition, many mycotoxins and fungal metabolites also directly promote carcinogenesis, for example, Candida albicans can product nitrosamine, acetaldehyde and candidalysin ( 157 ). Furthermore, a latest study has just found that not only bacterial microbiota (e.g., Fusobacterium ) but also fungal microbiota can affect chemotherapy resistance ( 158 ).…”
Section: The Role Of Clrs In Intestinal Carcinogenesismentioning
confidence: 99%
“…A growing number of studies report that inflammation can influence the dynamics and aggressiveness of still-forming malignancy [ 2 , 10 , 21 ]. Canonically, there are three main pathways of genetic instability and two morphological sequences of CRC carcinogenesis, which differ in pathogenesis and dynamics [ 10 , 23 , 24 ] ( Figure 1 ).…”
Section: Inflammation In the Pathways Of Sporadic And Colitis-associa...mentioning
confidence: 99%
“…In settings of reduced apoptotic stimuli and enhanced proliferation, the risk of genetic error increases, leading to the initiation of carcinogenesis [ 2 , 6 ]. The disruption in the cytokine-mediated crosstalk between immune and epithelial cells in the large bowel seems to be a major factor driving chronic inflammation and leading to the initiation and progression of large bowel cancers [ 21 ]. Epidemic studies seem to partly support the hypothesis that chronic inflammation accelerates the formation of cancer because colitis-associated cancers develop in younger patients, are often localized in the right colon, and are characterized by shorter overall survival [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, hepatic exposure to gut-derived microbiota-associated molecular patterns (MAMPs), such as lipopolysaccharide (LPS), promote hepatic inflammation, fibrosis, proliferation, as well as activation of anti-apoptotic signals [ 50 ]. Specifically, these MAMPs play a significant role in the activation of host pattern recognition receptors (PRRs) in the liver, especially the Toll-like receptor family (TLRs) [ 51 ]. Various types of hepatic cells express TLR4 in particular, including Kupffer cells, hepatic stellate cells (HSCs), and endothelial cells.…”
Section: Role Of the Microbiome On Inflammatory Processes In Hccmentioning
confidence: 99%